Peningkatan Literasi Digital Pelayanan PBB-P2 Berbasis Aplikasi SiPBB TRENGGINAS Melalui Pelatihan dan Pendampingan Bagi Aparatur Desa - Kurniawan, Arief Hendra; Hasan Albana, Maududy; Jihannindya, Luqy; Dwi Setyaningrum, Mareta; Widi Astutik, Mila; Dandy, Mohammad Azra; Alfarizi, Muhammad Rafi; Haqiqi, Ilham; Mada Lahiya, Ilham Putu; Arini, Jihan; Najmi Iftita Zuhrin, Mazaya; Zulaikah, Siti (Civiliza Publishing, 2025)
The advancement of information technology has had a significant impact on public services, including in the area of regional taxation. One of the innovations introduced by the Government of Magelang Regency is SIPBB Trengginas, a web-based application designed to facilitate the management of Land and Building Tax (PBB) data, expedite the data updating process, and enhance transparency at the village level. This community service activity was carried out through the thematic Community Service Program (KKN) in Trenten Village, aimed at improving the capacity of village officials in using SIPBB Trengginas, particularly in the features of rights transfer mutation and the addition of new objects. The method employed was hands-on practice, starting with basic training at the BPPKAD of Magelang Regency, followed by intensive assistance to village officials. The results of this activity indicate that the assistance was effective, as village officials were able to operate the mutation and new object addition features independently, allowing for faster and more accurate updates of PBB data. However, several challenges were encountered, such as a lack of understanding of the overall system workflow and varying levels of digital literacy among village officials. As a sustainability measure, the KKN team has developed and submitted a user guide module for SIPBB Trengginas to support self-learning and long-term utilization of the application.